Characterisation of flavour compounds formed by gamma-irradiation of polypropylene - Tyapkova, Oxana; Czerny, Michael; Büttner, Andrea (Polymer Degradation and Stability, 2009)
Sterilisation of plastic packaging materials for food, pharmaceutical or cosmetic products with 60Co γ-irradiation in the presence of oxygen can result in the formation of volatile substances. These may subsequently induce off-odours in these materials that might be regarded as negative by the consumers. Trace volatiles and odorous substances of polypropylene, irradiated with 60Co γ rays at 10 and 20 kGy, respectively, were collected and analysed by gas chromatography-olfactometry (GC-O), GC-MS and GC-GC-MS. The methodology was successfully applied for identification of 29 characteristic odorants in a non-irradiated control sample and 38 odorants in γ-irradiated polypropylene samples. Selected odour-active compounds were quantified using GC-GC-MS in combination with stable isotope dilution assays. The quantitative data mirrors the compositional changes in volatile odorous substances from polypropylene during treatment with ionising γ rays in a 60Co-irradiation plant. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.nat.dchph.llmch.charac
Keywords: γ-Irradiation; Aroma extract dilution analysis (AEDA); Gas chromatography-olfactometry (GC-O); Polypropylene (PP); Radiolysis products

Characterisation of flavour compounds formed by g-irradiation of polypropylene. - Tyapkova, Oxana; Czerny, Michael; Büttner, Andrea (Polymer Degradation and Stability, 2009)
Sterilisation of plastic packaging materials for food, pharmaceutical or cosmetic products with 60Co γ-irradiation in the presence of oxygen can result in the formation of volatile substances. These may subsequently induce off-odours in these materials that might be regarded as negative by the consumers. Trace volatiles and odorous substances of polypropylene, irradiated with 60Co γ rays at 10 and 20 kGy, respectively, were collected and analysed by gas chromatography–olfactometry (GC–O), GC–MS and GC–GC–MS. The methodology was successfully applied for identification of 29 characteristic odorants in a non-irradiated control sample and 38 odorants in γ-irradiated polypropylene samples. Selected odour-active compounds were quantified using GC–GC–MS in combination with stable isotope dilution assays. The quantitative data mirrors the compositional changes in volatile odorous substances from polypropylene during treatment with ionising γ rays in a 60Co-irradiation plant.<br

Characterisation of flavour-texture interactions in sugar-free and sugar-containing pectin gels. - Tyapkova, Oxana; Bader-Mittermaier, Stephanie; Schweiggert-Weisz, Ute; Wurzinger, Sandrina; Beauchamp, Jonathan; Büttner, Andrea (Food Research International, 2014)
The influences of sugar replacement with erythritol or erythritol/sucralose on textural properties (hardness and visco-elastic behaviour) and flavour release of low ester pectin gels containing 0.04% or 0.12% (w/w) calcium citrate were analysed. Flavour release of (Z)-hex-3-en-1-ol (cis-3-hexenol), benzaldehyde, ethyl butanoate and 2-methylpropyl 3-methylbutanoate (isobutyl isovalerate) was determined using proton-transfer-reaction mass spectrometry (PTR-MS). In-vitro studies showed that the replacement of sucrose with erythritol did not influence flavour release, whereas the release tended to be higher and faster for erythritol- or erythritol/sucralose-containing gels during in-vivo measurements. Additionally, different flavour release patterns were obtained between harder and softer pectin gels during in-vivo measurements, while only release of isobutyl isovalerate was significantly different during in-vitro analysis. The sensory analysis exhibited significant differences between the flavoured pectin gels with similar textures, confirming the results of PTR-MS measurements. Generally, flavour perception was reduced with increased gel hardness independently of the nose-space concentrations, reflecting perceptual interactions between texture and flavou

Characterisation of flavour-texture interactions in sugar-free and sugar-containing pectin gels - Tyapkova, Oxana; Bader-Mittermaier, Stephanie; Schweiggert-Weisz, Ute; Wurzinger, Sandrina; Beauchamp, Jonathan; Büttner, Andrea (Food Research International, 2014)
The influences of sugar replacement with erythritol or erythritol/sucralose on textural properties (hardness and visco-elastic behaviour) and flavour release of low ester pectin gels containing 0.04% or 0.12% (w/w) calcium citrate were analysed. Flavour release of (Z)-hex-3-en-1-ol ( cis-3-hexenol), benzaldehyde, ethyl butanoate and 2-methylpropyl 3-methylbutanoate (isobutyl isovalerate) was determined using proton-transfer-reaction mass spectrometry (PTR-MS).In-vitro studies showed that the replacement of sucrose with erythritol did not influence flavour release, whereas the release tended to be higher and faster for erythritol- or erythritol/sucralose-containing gels during in-vivo measurements. Additionally, different flavour release patterns were obtained between harder and softer pectin gels during in-vivo measurements, while only release of isobutyl isovalerate was significantly different during in-vitro analysis. The sensory analysis exhibited significant differences between the flavoured pectin gels with similar textures, confirming the results of PTR-MS measurements. Generally, flavour perception was reduced with increased gel hardness independently of the nose-space concentrations, reflecting perceptual interactions between texture and flavour. © 2013 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.charac
Keywords: Erythritol; Flavour release; Pectin gel; PTR-MS; Rheology; Texture

Flavor release from sugar-containing and sugar-free confectionary egg albumen foams - Tyapkova, Oxana; Siefarth, Caroline; Schweiggert-Weisz, Ute; Beauchamp, Jonathan; Büttner, Andrea; Bader-Mittermaier, Stephanie (Lwt-Food Science and Technology, 2016)
The flavor release of two egg albumen foams containing different combinations of polyols and bulking agents was investigated in relation to the physicochemical properties of the foams in comparison to a sugar-containing and a sugar-free reference. The in vitro and in vivo release of four flavor compounds, namely (Z)-hex-3-en-1-ol, benzaldehyde, ethyl butanoate, and 2-methylpropyl 3-methylbutanoate was investigated using proton-transfer-reaction mass spectrometry (PTR-MS). Foam density was highest for the sugar-free reference (294.5 g L−1) and lowest for the sugar-containing protein foam (193.2 g L−1), whereas egg albumen foams with combinations of polyols and bulking agents revealed medium foam densities (212.2 g L−1 and 217.9 g L−1). Flavor release was affected by foam density to a significantly higher extent than by foam firmness, whereby decreased in vitro and increased in vivo flavor release with increased foam density was observed for all compounds. The flavor release data were also in good agreement with the perceived aroma intensities, supporting the role of texture-flavor interactions in perception. This study highlights the impact that complex interactions of physical and chemical properties have on flavor release, with the egg albumen foams representing complex aerated food matrices commonly used for confectionery product
Keywords: Erythritol; Maltitol; Rheology; Density; Flavor release

Influence of polyols and bulking agents on flavour release from low-viscosity solutions. - Siefarth, Caroline; Tyapkova, Oxana; Beauchamp, Jonathan; Schweiggert, Ute; Büttner, Andrea; Bader, Stephanie (Food Chemistry, 2011)
The release of four volatile flavour compounds (cis-3-hexen-1-ol, benzaldehyde, ethyl butanoate and butyl isovalerate) from pure water and various low-viscosity aqueous solutions (sucrose, maltitol, erythritol, polydextrose and oligofructose, each at 20% (w/w)) was investigated. Dynamic headspace concentrations of the flavour compounds at thermodynamic equilibrium were monitored by proton-transfer-reaction mass spectrometry (PTR-MS). The rheological properties of the solutions were characterised by their viscosity. Flavour release from pure water increased with increasing hydrophobicity and volatility of the flavour compounds. The highly volatile compounds were retained more extensively in the presence of sucrose, polyols and bulking agents, compared to in pure water, whereas an increase in the release of the less volatile cis-3-hexen-1-ol was observed. All aqueous solutions had similar viscosities, although bulking agent solutions tended to have higher viscosities than polyol solutions of the same concentration. A correlation between viscosity and flavour release in the low-viscosity solutions was not evident.<br

Influence of polyols and bulking agents on flavour release from low-viscosity solutions - Siefarth, Caroline; Tyapkova, Oxana; Beauchamp, Jonathan; Schweiggert, Ute; Büttner, Andrea; Bader, Stephanie (Food Chemistry, 2011)
The release of four volatile flavour compounds (cis-3-hexen-1-ol, benzaldehyde, ethyl butanoate and butyl isovalerate) from pure water and various low-viscosity aqueous solutions (sucrose, maltitol, erythritol, polydextrose and oligofructose, each at 20% (w/w)) was investigated. Dynamic headspace concentrations of the flavour compounds at thermodynamic equilibrium were monitored by proton-transfer-reaction mass spectrometry (PTR-MS). The rheological properties of the solutions were characterised by their viscosity. Flavour release from pure water increased with increasing hydrophobicity and volatility of the flavour compounds. The highly volatile compounds were retained more extensively in the presence of sucrose, polyols and bulking agents, compared to in pure water, whereas an increase in the release of the less volatile cis-3-hexen-1-ol was observed. All aqueous solutions had similar viscosities, although bulking agent solutions tended to have higher viscosities than polyol solutions of the same concentration. A correlation between viscosity and flavour release in the low-viscosity solutions was not evident. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Bulking agent; Flavour release; Polyol; Viscosity; PTR-MS

Mixture design approach as a tool to study in vitro flavor release and viscosity interactions in sugar-free polyol and bulking agent solutions. - Siefarth, Caroline; Tyapkova, Oxana; Beauchamp, Jonathan; Schweiggert-Weisz, Ute; Büttner, Andrea; Bader-Mittermaier, Stephanie (Food Research International, 2011)
Flavor release from mixtures of maltitol, erythritol, polydextrose and oligofructose dissolved in water at concentrations of 43% (w/w) was investigated to analyze possible interactions between the viscous matrix and the volatiles using an experimental mixture design in combination with data analysis and response modeling tools. The dynamic release of four flavor compounds (cis-3-hexenol, benzaldehyde, ethyl butanoate and butyl isovalerate) from the matrices at 37 °C was determined by headspace analyses using proton-transfer-reaction mass spectrometry (PTR-MS). The aim of the present study was to understand the complex release mechanisms from high-viscosity polyol and bulking agent solutions for the intention of conducting further studies on flavor release from sugar-free confectionary products. Each of the non-volatiles had a significant effect (p < 0.05) on flavor release with regression coefficients (R²) between 0.72 and 0.93 for the release parameters Imax, t½, and Δc/Δt, and 0.99 for viscosity. However, the magnitude of influence varied between the bulking agents and polyols due to their different molecular weights. A clear correlation between viscosity of the solutions and flavor release was found, revealing complex matrix-volatile interactions in the high-viscosity solutions. The release of all investigated flavor compounds decreased when the viscosity of the solutions increased. Therefore, it is assumed that the flavor release is significantly influenced by the non-volatiles when a critical concentration (c*) is exceeded. Interactions between the sugar substitutes were found to affect the viscosity of the matrices, whereas flavor release was not affected by interactions between the polyols and bulking agents investigated.<br

Mixture design approach as a tool to study in vitro flavor release and viscosity interactions in sugar-free polyol and bulking agent solutions - Siefarth, Caroline; Tyapkova, Oxana; Beauchamp, Jonathan; Schweiggert, Ute; Büttner, Andrea; Bader, Stephanie (Food Research International, 2011)
Flavor release from mixtures of maltitol, erythritol, polydextrose and oligofructose dissolved in water at concentrations of 43% (w/w) was investigated to analyze possible interactions between the viscous matrix and the volatiles using an experimental mixture design in combination with data analysis and response modeling tools. The dynamic release of four flavor compounds (cis-3-hexenol, benzaldehyde, ethyl butanoate and butyl isovalerate) from the matrices at 37 degrees C was determined by headspace analyses using proton-transfer-reaction mass spectrometry (PTR-MS). The aim of the present study was to understand the complex release mechanisms from high-viscosity polyol and bulking agent solutions for the intention of conducting further studies on flavor release from sugar-free confectionary products. Each of the non-volatiles had a significant effect (p < 0.05) on flavor release with regression coefficients (R(2)) between 0.72 and 0.93 for the release parameters I(max), t(1/2), and Delta c/Delta t, and 0.99 for viscosity. However, the magnitude of influence varied between the bulking agents and polyols due to their different molecular weights. A clear correlation between viscosity of the solutions and flavor release was found, revealing complex matrix-volatile interactions in the highviscosity solutions. The release of all investigated flavor compounds decreased when the viscosity of the solutions increased. Therefore, it is assumed that the flavor release is significantly influenced by the nonvolatiles when a critical concentration (c*) is exceeded. Interactions between the sugar substitutes were found to affect the viscosity of the matrices, whereas flavor release was not affected by interactions between the polyols and bulking agents investigated. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Critical concentration (c*); Experimental mixture design; Flavor release; Matrix-flavor-interactions; PTR-MS; Viscosity

Performance assessment of proton-transfer-reaction time-of-flight mass spectrometry (PTR-TOF-MS) for analysis of isobaric compounds in food-flavour applications. - Zardin, Erika; Tyapkova, Oxana; Büttner, Andrea; Beauchamp, Jonathan (Lwt-Food Science and Technology, 2014)
Characterisation of food-flavour release using quadrupole-based on-line mass spectrometers such as proton-transfer-reaction mass spectrometry (PTR-MS, or PTR-QMS) can be complicated when nominally isobaric aroma compounds are present in complex food matrices. The recent combination of PTR-MS with time-of-flight mass spectrometry (PTR-TOF-MS) offers an analytical tool potentially capable of overcoming this problem because of its enhanced mass resolution. In this context, four pairs of isobaric compounds (cis-3-hexenol and 2,3-pentanedione, benzaldehyde and m-xylene, ethyl butanoate and 2-methylbutanol, and isobutyl isopentanoate and 1-hexanol) were investigated by PTR-TOF-MS to assess its mass-resolving power for food-flavour applications. Headspace analyses of aqueous solutions containing nominally isobaric aroma compounds that are unresolvable by PTR-QMS demonstrated that the PTR-TOF-MS mass-resolving power, which is m/z-dependent, enabled discrimination between isobaric peaks at a centre of mass separation down to at least 0.030 Da. Visual discrimination between these isobaric compound peaks in the headspace of aqueous solutions down to a concentration range of a few tens of ng mL−1 was also possible, enabling an empirical method for determining the limit of quantitation in solution for single compounds. PTR-TOF-MS offers distinct advantages over conventional PTR-MS for certain flavour release applications.<br

Performance assessment of proton-transfer-reaction time-of-flight mass spectrometry (PTR-TOF-MS) for analysis of isobaric compounds in food-flavour applications - Zardin, Erika; Tyapkova, Oxana; Büttner, Andrea; Beauchamp, Jonathan (Lwt-Food Science and Technology, 2014)
Characterisation of food-flavour release using quadrupole-based on-line mass spectrometers such as proton-transfer-reaction mass spectrometry (PTR-MS, or PTR-QMS) can be complicated when nominally isobaric aroma compounds are present in complex food matrices. The recent combination of PTR-MS with time-of-flight mass spectrometry (PTR-TOF-MS) offers an analytical tool potentially capable of overcoming this problem because of its enhanced mass resolution. In this context, four pairs of isobaric compounds (cis-3-hexenol and 2,3-pentanedione, benzaldehyde and m-xylene, ethyl butanoate and 2-methylbutanol, and isobutyl isopentanoate and 1-hexanol) were investigated by PTR-TOF-MS to assess its mass-resolving power for food-flavour applications. Headspace analyses of aqueous solutions containing nominally isobaric aroma compounds that are unresolvable by PTR-QMS demonstrated that the PTR-TOF-MS mass-resolving power, which is m/z-dependent, enabled discrimination between isobaric peaks at a centre of mass separation down to at least 0.030Da. Visual discrimination between these isobaric compound peaks in the headspace of aqueous solutions down to a concentration range of a few tens of ngmL-1 was also possible, enabling an empirical method for determining the limit of quantitation in solution for single compounds. PTR-TOF-MS offers distinct advantages over conventional PTR-MS for certain flavour release applications. © 2013 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.perfor
Keywords: Flavour release; Isobaric compounds; Limit of quantitation; PTR-TOF-MS